Liberty and Order - Banning, Lance, 1942-2006 (Book collections on Project MUSE., 2004)
Liberty and Order is an ambitious anthology of primary source writings: letters, circulars, debate transcriptions, House proceedings, and newspaper articles that document the years during which America's founding generation divided over the sort of country the United States was to become. The founders' arguments over the proper construction of the new Constitution, the political economy, the appropriate level of popular participation in a republican polity, foreign policy, and much else, not only contributed crucially to the shaping of the nineteenth-century United States, but also have remained of enduring interest to all historians of republican liberty. This anthology makes it possible to understand the grounds and development of the great collision, which pitted John Adams, Alexander Hamilton, and others who called themselves Federalists or, sometimes, the friends of order, against the opposition party led by Thomas Jefferson, James Madison, and their followers, in what emerged as the Jeffersonian Republican Party. Editor Lance Banning provides the reader with original-source explanations of early anti-Federalist feeling and Federalist concerns, beginning with the seventh letter from the 'Federal Farmer', in which the deepest fears of many opponents of the Constitution were expressed. He then selects from the House proceedings concerning the Bill of Rights and makes his way toward the public debates concerning the massive revolutionary debt acquired by the United States. The reader is able to examine the American reaction to the French Revolution and to the War of 1812, and to explore the founders' disagreements over both domestic and foreign policy. The collection ends on a somewhat melancholy note with the correspondence of Jefferson and Adams, who were, to some extent, reconciled to each other at the end of their political careers. Brief, elucidatory headnotes place both the novice and the expert in the midst of the times. - Back cover.